Comparison of the immunogenicity and safety of polysaccharide and protein-conjugated pneumococcal vaccines among the elderly aged 80 years or older in Japan: An open-labeled randomized study. Issue 2 (3rd January 2015) - Namkoong, Ho; Funatsu, Yohei; Oishi, Kazunori; Akeda, Yukihiro; Hiraoka, Rika; Takeshita, Kei; Asami, Takahiro; Yagi, Kazuma; Kimizuka, Yoshifumi; Ishii, Makoto; Tasaka, Sadatomo; Suzuki, Yukio; et al.
Highlights Increase in GMCs of serotype-specific IgG levels in PCV7 group. Increase in GMTs of OIs of serotype-specific IgG levels in PCV7 group. Our study confirmed the safety of both PCV7 and PPV23 vaccines in elderly people. PCV7 displayed superior immunogenicity than PPV23 in 4/7 serotypes included in PCV7.